1986
DOI: 10.1139/o86-103
|View full text |Cite
|
Sign up to set email alerts
|

Persulfide sulfur is a growth factor for cells defective in sulfur metabolism

Abstract: Several systems which generate persulfide sulfur promote in vitro proliferation of L1210 murine lymphoma cells. The systems include cysteine disulfides and pyridoxal, cystamine and diamine oxidase, beta-mercaptoalcohol disulfides and an alcohol dehydrogenase, and sulfide-treated proteins and a thiol. Persulfide sulfur is very unstable at pH near 7 and an essential feature of the growth-supporting systems is the ability to generate persulfide sulfur at a very low rate for long periods of time. Methyl disulfides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 0 publications
1
53
0
Order By: Relevance
“…In 1975, one of the present authors (JT) confirmed this growth factor effect with several members of a bank of murine cell lines and showed that the sulfur compounds fall into two categories [16]. As shown in Figure 3, three xenobiotic sulfur compounds, MER, TGL, and TEA (cysteamine, 2-mercapto-1-aminoethane, thioethanolamine) stimulate growth under the following conditions: (a) at μM concentrations; (b) only in the oxidized (disulfide) form [17]; and (c) with any serum (or bovine serum albumin) replacing fetal calf serum.…”
Section: Sulfur As a Regulatory Agentmentioning
confidence: 84%
“…In 1975, one of the present authors (JT) confirmed this growth factor effect with several members of a bank of murine cell lines and showed that the sulfur compounds fall into two categories [16]. As shown in Figure 3, three xenobiotic sulfur compounds, MER, TGL, and TEA (cysteamine, 2-mercapto-1-aminoethane, thioethanolamine) stimulate growth under the following conditions: (a) at μM concentrations; (b) only in the oxidized (disulfide) form [17]; and (c) with any serum (or bovine serum albumin) replacing fetal calf serum.…”
Section: Sulfur As a Regulatory Agentmentioning
confidence: 84%
“…The defective metabolism of methylthioadenosine in these cells results in an inability to form 2-keto-4-(methylthio)butyric acid, while this precursor of CH3SH is clearly generated in proliferating, nonsulfhydryl-dependent, murine cell lines (52). Systems slowly providing persulfide sulfur effective as a growth factor in vitro include the nonenzymatic reaction of cystine with pyridoxal phosphate (5), the oxidation of cystamine catalyzed by diamine oxidase (53,54), the oxidation of mercaptoalcohol disulfides catalyzed by alcohol dehydrogenase (31), and crystalline bovine serum albumin and globulin converted by sulfide treatment (55) to persulfide-containing proteins; glutathione additions are required for growth factor activity of the latter.…”
Section: Resultsmentioning
confidence: 99%
“…2-4,35-39 A recent assessment of these two potential end products concluded that bioactivity is due to sulfane sulfur, not H 2 S. 35,42 However, other sulfhydryls-N-acetyl-cysteine, reduced lipoic acid, glutathione, d-penicillamine or their disulfides, which are not known to generate H 2 S or sulfane sulfur [1,2]-have process-altering capabilities, including cancer. [43][44][45][46] Thus, the bioactivity moiety of sulfhydryl/disulfides needs to be left unresolved; perhaps the best take home message is that suggested for structurally unique, food organosulfurs-several mechanisms are likely.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, it would simplify mechanistic studies if the etiologic agent were known; hopefully this will become defined by non-retired investigators. Until then, alternative explanations for the extended latency period for BXSB-Yaa + and complete prevention by 2-Me were (1) tumors are a result of non-viral etiologic agents; (2) (5) other, as yet to be clarified, genetic differences, some of which were postulated to control specific antitumor immunological processes. 52 It is important to note that mice with an H-2 b haplotype, as well as male mice, can develop mammary tumors due to exogenous MMTVs 53 and that other strains develop mammary tumors via age-associated recombination/activation of endogenous Mtvs.…”
Section: Bxsb-yaamentioning
confidence: 99%
See 1 more Smart Citation